NILAI RELIGIUS TOKOH LANGIT DALAM NOVEL LINTANG LANGIT PADA SENJA KARYA RIRIN ASTUTININGRUM - Slamet Hariyadi; Muhammad Hasbullah Ridwan (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2020)
Religious value is a person's religious value towards absolute divine truth, religious values are also reflected in everyday life as well as speaking well, having good morals, ethics, politeness towards people who are older than him. The formulation of the problem in this research has three aspects, namely (1) How is the religious value of the character Langit and his God in the novel Lintang Langit Pada Senja by Ririn Astutiningrum. (2) How is the religious value of the character Langit and his fellows in the novel Lintang Langit at Senja by Ririn Astutiningrum. (3) How is the religious value of the character Langit with nature in the novel Lintang Langit at Senja by Ririn Astutiningrum. The objectives of this study are: (1) To describe the religious values of the character Langit and his God in the novel Lintang Langit Pada Senja by Ririn Astutiningrum. (2) Describing the religious value of the character Langit and his fellows in the novel Lintang Langit at Senja by Ririn Astutiningrum. (3) Describing the religious values of Langit and nature in the novel Lintang Langit at Senja by Ririn Astutiningrum.This study uses a descriptive qualitative method using a Sociology of Literature approach. Research that looks for verbal data in the form of written words or sentences that show the attitude of life and behavior of the main character (Langit) in the novel Lintang Langit at Senja by Ririn Astutiningrum.The conclusion of the novel Lintang Langit at Senja by Ririn Astutiningrum is a work of fiction that serves to provide an inner experience of moral values. In religious values reflect various things related to life problems that are expressed through the attitudes and behavior of the characters. These noble qualities are: The religious values of the main character of Langit and his God in the form of piety, patience, sincerity and faith. The religious values of the main character of Langit towards others in the form of compassion, togetherness in life, respect for others and fairness to others. The religious value of the main character of Langit with nature in the form of protecting and preserving the natural environment.